Design System Foreign Currency Exchange In CV. Frizindo Prima Using Visual Basic 6.0 - Fariz Fatullah (Jurnal Sistem Informasi, 2006)
This explains the scientific writing about the design of application programs of foreign exchange transactions by using programming language Visual Basic 6.0 is accompanied by the flow diagram (flowchart). In scientific writing database is used also by using the Visual Data Manager program which has been integrated in the Visual Basic 6.0 program itself. Consists of 4 tables of Currency, Customer, Transaction, Employee. In the end the design program of foreign exchange transactions system will be applied to the CV. Prima Frizindo to ease in conducting transactions, such as making notes and making the transaction report.